ANALISIS SWOT DAKWAH PIMPINAN DAERAH MUHAMMADIYAH REJANG LEBONG DALAM MEWUJUDKAN ISLAM BERKEMAJUAN - alfiyyah Nur Dhoifullah (Fakultas Agama Islam Universitas Muhammadiyah Bengkulu, 2020)
ABSTRACT The regional Leadership of Muhammadiyah in Lebong Rejang regence is required to understand broadly and deeply the concept of progressive Islam and realize it in society. In actualizing this is needed to do SWOT analysis. This research method was descriptive qualitative method by focusing on the preaching of progressive islam in society. Data were obtained by interview some questions and then conclude the results how to preach and actualize the progressive Islam. Based on the results of the interview, the researcher used SWOT analysis toward the preaching that has beed excuting in society. Progress of Da’wah progressive Islam has not been well realized and has not been significant. Regional Leader of Muhammadiyah Rejang Lebong has the power to realize that programs; weaknesses occur in preaching activities through arts or social media and tolerance to worship. Opportunities has social institutions, such as LazisMU and many fields of health and education. Threats.there is a lack of human resources to use technology as a medium for da'wah. Keywords: Da'wah, Muhammadiyah, Progressive Islam